The influence of media on public perception of covid-19: case study on youth in Klang Valley. - Lee, Zhi Ying (2024)

(untitled)
This research aims to explore the influence of media channels on public perception towards Covid19 among youth aged between 15 to 40 years old living in the Klang Valley area. In this era of globalization, various media channels have become a part of our daily lives and has substantive impacts on our perception. Throughout the Covid-19 pandemic, media platforms have become an essential platform to disseminate information and opinions related to the disease as it offers immediacy. However, the information on the various media channels may be a source of misinformation in many communities as some information are false and inaccurate. This study will employ quantitative survey via Google Form to understand the perception of Covid-19 with the influence of media channels among youth and qualitative observation on media channels regarding information of Covid-19. Therefore, the objective of this research is to examine how various media channels contribute to the public perception of Covid-19 positively and negatively.